Climatic Risk and Distribution Atlas of European Bumblebees - Oliver Schweiger (BioRisk, 2015)
Bumble bees represent one of the most important groups of pollinators. In addition to their ecological and economic relevance, they are also a highly charismatic group which can help to increase the interest of people in realizing, enjoying and conserving natural systems. However, like most animals, bumble bees are sensitive to climate. In this atlas, maps depicting potential risks of climate change for bumble bees are shown together with informative summary statistics, ecological background information and a picture of each European species. Thanks to the EU FP7 project STEP, the authors gathered over one million bumblebee records from all over Europe. Based on these data, they modelled the current climatic niche for almost all European species (56 species) and projected future climatically suitable conditions using three climate change scenarios for the years 2050 and 2100. While under a moderate change scenario only 3 species are projected to be at the verge of extinction by 2100, 14 species are at high risk under an intermediate change scenario. Under a most severe change scenario as many as 25 species are projected to lose almost all of their climatically suitable area, while a total of 53 species (77% of the 69 European species) would lose the main part of their suitable area. Climatic risks for bumblebees can be extremely high, depending on the future development of human society, and the corresponding effects on the climate. Strong mitigation strategies are needed to preserve this important species group and to ensure the sustainable provision of pollination services, to which they considerably contribute.